4(a-11)-7(2a+1)=-2.28

Simple and best practice solution for 4(a-11)-7(2a+1)=-2.28 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(a-11)-7(2a+1)=-2.28 equation:


Simplifying
4(a + -11) + -7(2a + 1) = -2.28

Reorder the terms:
4(-11 + a) + -7(2a + 1) = -2.28
(-11 * 4 + a * 4) + -7(2a + 1) = -2.28
(-44 + 4a) + -7(2a + 1) = -2.28

Reorder the terms:
-44 + 4a + -7(1 + 2a) = -2.28
-44 + 4a + (1 * -7 + 2a * -7) = -2.28
-44 + 4a + (-7 + -14a) = -2.28

Reorder the terms:
-44 + -7 + 4a + -14a = -2.28

Combine like terms: -44 + -7 = -51
-51 + 4a + -14a = -2.28

Combine like terms: 4a + -14a = -10a
-51 + -10a = -2.28

Solving
-51 + -10a = -2.28

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '51' to each side of the equation.
-51 + 51 + -10a = -2.28 + 51

Combine like terms: -51 + 51 = 0
0 + -10a = -2.28 + 51
-10a = -2.28 + 51

Combine like terms: -2.28 + 51 = 48.72
-10a = 48.72

Divide each side by '-10'.
a = -4.872

Simplifying
a = -4.872

See similar equations:

| Z+6.8=15 | | -4.8f+6.8=-8.48 | | 8=7-2(7x+2) | | 3-2x=1-3x | | x^2=10(10-x) | | 10-1.4x=10.84 | | 25=r-3 | | -16+2x=-32+12x | | 26+9n=264 | | x^2=100-10x | | 5(4+x)=6+3x | | 7(2-3a)=3(5a-1) | | x(3x+2)=1496 | | 3x+2y=12fory | | t^2+2t-14=0 | | 3x+8=-70-10 | | -2.8(x+4.9)=8.2 | | 8s^2-6s=2s | | 3(x+4)+2=5 | | 5z-3=1 | | 10x^2=100(10-x) | | 9x^2=-36 | | 52-3x=12-8x | | 9x-(2x-5)=4x+11 | | 8-2(4-x)=2x+5-3 | | 5p^2=12-10p | | 3(-6x+9)10x=1 | | 3m-10=25-4m | | 7(7-x)=133 | | 6x+8=-40-2x | | 3x^2-45x=-168 | | 2x-5y-6z= |

Equations solver categories